2018
DOI: 10.18203/2320-6012.ijrms20184404
|View full text |Cite
|
Sign up to set email alerts
|

A study to compare the efficacy of intermittent versus continuous regimen of pantaprazole in the management of upper gastrointestinal bleed (non variceal)

Abstract: Background: UGI bleeding is defined as bleeding that occurs in the digestive tract proximal to the ligament of treitz. Intermittent dosage regimen IV bolus and high dose IV continuous infusion forms helps in achieving and maintaining this pH goal of more than 6 which forms optimal environment for peptic ulcer healing and clot stabilization to occur. Theoretically, high-dose IV continuous infusion should provide the most potent acid suppression. Aims and objective was to compare the efficacy of intermittent dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…This result was not statistically significant. 17 Furthermore, Ibrahim et al 18 carried out a randomized double-blind study to compare the advantage of high and standard- dose omeprazole (IV omeprazole 40 mg bolus dose once daily followed by normal saline infusion vs IV bolus of 80 mg omeprazole followed by 8 mg/h infusion) as prophylaxis against upper GIT bleeding in high risk critically ill patients. It was found that patients on high dose omeprazole had higher gastric pH, lower incidence of critical significant GIT bleeding, higher ICU stay Hb, lower number of RBCs transfusion and shorter ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…This result was not statistically significant. 17 Furthermore, Ibrahim et al 18 carried out a randomized double-blind study to compare the advantage of high and standard- dose omeprazole (IV omeprazole 40 mg bolus dose once daily followed by normal saline infusion vs IV bolus of 80 mg omeprazole followed by 8 mg/h infusion) as prophylaxis against upper GIT bleeding in high risk critically ill patients. It was found that patients on high dose omeprazole had higher gastric pH, lower incidence of critical significant GIT bleeding, higher ICU stay Hb, lower number of RBCs transfusion and shorter ICU stay.…”
Section: Discussionmentioning
confidence: 99%